Formation mechanism of asymmetric porous polymer films by photoinduced phase separation in the presence of solvent. Issue 34 (2nd May 2019) - Yoshihara, Hirokazu; Yamamura, Masato
ABSTRACT: Photoinduced phase separation in the presence of a nonreactive volatile solvent provides a simple, light‐tunable, and cost‐effective route for fabrications of porous polymer films. Here, we show that the short‐time (<10 s) ultraviolet irradiation of a photoreactive solution film promotes particular asymmetries in the composition and porosity across the thickness. Confocal Raman spectroscopy revealed that the compositional asymmetry is maximum at a certain critical light intensity. We discuss the film formation mechanism based on the light‐driven diffusion of the solvent and monomer. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47867. Abstract :